THE EFFECT ACCOUNTING CONSERVATISM USING LO_EKO MODEL - Marselinus Asri (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
The purpose research is to examine other variables that also affect the relationship between conservatism and earnings quality. Data population are companies listed in Indonesia Stock Exchange during the period 2014-2017. The sample selection is based on purposive sampling method with the purpose of obtaining a representative sample. The results of this study indicate that the Instrumental Variables Conservatism has a significant positive effect on the Earning Quality. This means that management positively signals the application of accounting conservatism within the company and has an impact on improving the quality of earnings. The next investor is expected to provide more valuations by providing a high premium for the company's stock price.